Legendary rivals : collegiality and ambition in the tales of early Rome - Neel, Jaclyn. (Mnemosyne, Supplements, 2015)
In Legendary Rivals Jaclyn Neel argues for a new interpretation of the foundation myths of Rome. Instead of a negative portrayal of the city's early history, these tales offer a didactic paradigm of the correct way to engage in competition. Accounts from the triumviral period stress the dysfunctional nature of the city's foundation to capture the memory of Rome's civil wars. Republican evidence suggests a different emphasis. Through diachronic analyses of the tales of Romulus and Remus, Amulius and Numitor, Brutus and Collatinus, and Camillus and Manlius Capitolinus, Neel shows that Romans of the Republic and early Principate would have seen these stories as examples of competition that pushed the bounds of propriety.